Implementasi Algoritma Zhu Takaoka Pada Aplikasi Sinopsis Film Bioskop Berbasis Mobile - Siahaan, Roni Daniel (TIN: Terapan Informatika Nusantara, 2021)
Cinema is a place for people to enjoy film shows, where the audience devotes all their feelings to the living picture being witnessed. The audience will witness a story that seems real in front of them. Cinema is one of the many alternatives for someone to have a recreation. The sharpness and sound effects of the cinema also greatly determine the satisfaction of the public who is watching a film show as personal entertainment. A cinema film synopsis is a summary that becomes a picture of a cinema film. Synopsis of cinema films can be an attraction for cinema lovers before watching cinema films because the summary of cinema films in the synopsis, cinema lovers can find out the information on films that will be screened on a bisokop. Based on time, many new cinema films will be shown in a cinema. This makes the synopsis of cinema films more and more and makes it difficult for the public to find a synopsis of a particular cinema in a short and precise time in order to find information on the title of the movie theaters are looking for